Pengaruh variasi sumber kalor terhadap besarnya laju perpindahan kalor melalui dinding komposit - Rudi Hariyanto; Mohamad Ma'ruf (University of Merdeka Malang, 2003)
Heat transfer is the study of how heat moves or flows from a place with a high temperature to a lower temperature so that heat can move due to a